Photocatalytic degradation of methylene blue using mixture of zinc oxide and activated carbon from rambutan peel - Dousi, Deidree Jane, 1993-, author; Rusmidah Ali, supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2016